Legal Analysis of Saddam Hussein's Individual Responsibility in the Subject of International Law - Elvita Septia Liza; Padrisan Jamba (International Journal of Law, Crime and Justice, 2025)
This article analyzes Saddam Hussein's individual responsibility as a subject of international law based on crimes committed during his rule in Iraq. Saddam Hussein was charged with various serious crimes such as war crimes, crimes against humanity, and genocide. This review covers relevant international legal instruments, Saddam Hussein's trial process, as well as criticism of the legitimacy and fairness of the trial. This research highlights the importance of applying the principle of individual responsibility in international law to uphold justice and prevent impunity for state leaders who commit serious violations. Apart from that, this article also discusses the challenges faced by the international justice system in dealing with cases involving heads of state, as well as the implications of court decisions for the development of international law and global human rights enforcement. In this way, this study seeks to provide a deeper understanding of the evolution of international criminal responsibility, as well as its role in preventing similar atrocities in the future.